Longitudinal Observations of Infants' Daily Arrivals at a Day Care Center - Willis, E. Anne.; Ricciuti, Henry N.; Cornell Univ., Ithaca, NY. Cornell Research Program in Early Development and Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This longitudinal study was concerned with infants' reactions to being greeted by a caregiver upon arrival at the nursery, being left by the parent with the caregiver, and to reunion with the parents. Observations were made twice weekly in the natural setting of the nursery foyer where parents normally arrive with their infants. An affectivity scale included in the appendix was used to rate infants' reactions. Subjects were 7 girls and three boys who were assigned to three groups: four half-day older infants whose mean age at entry into day care was 5.1 months; three full-day babies whose average entry age was 4.7 and three full-day younger babies whose average entry age was 2.7. Study findings tended to support the critical importance of stability and continuity in the people giving care to babies outside the home. Entry into day care at a younger age and a shorter daily separation are indicated as factors which may facilitate the baby's daily adjustment to day care. (MS)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Sponsoring Agency: CEMREL, Inc., St. Ann, MO.
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: NE-C-00-3-0103.
ERIC Note: Filmed from best available copy.
Educational level discussed: Preschool Education.
Keywords: Affective Behavior; Attachment Behavior; Child Caregivers; Day Care; Day Care Centers; Infant Behavior; Infants; Longitudinal Studies; Observation; Parent Child Relationship; Parents; Preschool Education; Rating Scales; Reports, Research